Elevated neutrophil-to-lymphocyte ratio: A marker for potential short-term neurological deterioration in acute large vessel occlusion patients postmechanical thrombectomy - Yanling Wang; Xiaokun Geng; Zhe Cheng; Fengwu Li; Yuchuan Ding (Wolters Kluwer Medknow Publications, 2023)
Objective: This study aimed to determine the risk factors associated with short-term neurological decline in acute ischemic stroke patients with large vessel occlusion (LVO) who have undergone successful endovascular recanalization through mechanical thrombectomy. Subjects and Methods: We included 168 LVO patients who had successful recanalization in this study. We collected the patients' demographic data and related disease test results. We noted the National Institutes of Health Stroke Scale (NIHSS) scores at the onset and on the 7th day postonset. After comparing the NIHSS scores at these two time points, we analyzed the correlation between the collected data and the NIHSS scores. We selected the logistic regression model variables based on the correlation significance. We included gender, age, diastolic blood pressure, glycosylated hemoglobin, urea nitrogen, hemoglobin, neutrophil-to-lymphocyte ratio (NLR), low-density lipoprotein, and total protein in a logistic regression model. We used the receiver operating characteristic (ROC) curve to evaluate the predictive power of NLR for deterioration. Results: Mechanical thrombectomy significantly lowered the median NIHSS score of LVO patients on the 7th day of onset, while a subset of patients experienced an increased NIHSS score. Correlation analysis revealed significant correlations between the NIHSS score at onset and diastolic pressure, white blood cell count, neutrophil count, creatinine, and urea nitrogen. On the 7th day postonset, NIHSS scores showed significant correlations with glycosylated hemoglobin, white blood cell count, neutrophil count, NLR, red blood cell count, hemoglobin, and urea nitrogen. Logistic regression analysis further revealed that patients with higher NLR are at significantly increased risk of short-term neurological decline. ROC analysis indicated that a higher NLR can serve as a diagnostic marker for potential adverse outcomes of mechanical thrombectomy. Conclusion: While mechanical thrombectomy substantially improves neurological deficits in LVO patients, some patients still experience deterioration. Higher NLR at stroke onset is associated with short-term neurological function decline in acute LVO patients postsuccessful recanalization.